Der Blick als literarischer Ausdruck der Wiener Moderne. Hugo von Hofmannsthals Klytämnestra: [The Gaze as Literary Expression in Viennese Modernism. Hugo von Hofmannsthal’s Clytemnestra] (Studia austriaca, 2018)
This article focuses on the character of Clytemnestra in Hugo von Hofmannsthal’s drama «Electra» and tries to answer two main questions. Which time-specific and ideological traits emerge from his interpretation of the character? How does the author deal with one of the most popular ancient figures and which aims does he link to his elaboration? It will be argued that Clytemnestra’s presentation and declamations make her a “modern child” of antiquity and that Hofmannsthal presents contemporary questions by having recourse to the ancient Greek tradition.